(3CKQ EdJRGe eOjQ GdeDSSI GdJQHhjI TQhW hXjaJg aj JYRjR OGaYjI GdeYdejf (B((3feGPL ef HYV eJhSWGJ bVGA GdfHWjI(B).s - g ((3HjQhJs (3LGeYI GdbOjS jhSas, 2013)
(3JgOa GdOQGSI Edi JMbjb eG jdj(B: 1) (3GdJYQa Ydi CfeGW GdEOGQI GdeOQSjI, (B2) (3GdJYQa Ydi GdegGQGJ hGdcaGjGJ GdeWdhH JhGaQgG aj eOjQ GdeOQSI (B. 3) (3GdJYQa Ydi CSGdjH GNJjGQ eOjQ GdeOQSI(B. 4) (3GdJYQa Ydi NUGFU GdOGaYjI hCgejJgG hhXGFagG(B. 5) (3GdJYQa Ydi fXQjGJ GdOGaYjI hJaSjQgG(B. 6) (3GdJYQa Ydi cjajI HfGA GdOGaYjI YfO GdeYdejf(B. 7) (3Jdbj GdVhA Ydi Cge GdXQha hGdYhGed GdJj jhGLggG GdeYdehf aj GdeOGQS ef CLd GdMO ef NWhQJgG(B. 7) (3Jdbj GdVhA Ydi GdMGLGJ GdMbjbjI ddeYdejf ef CLd JMSjfgG hJWhjQgG(B. (3Je GSJNOGe GdefgL GdhUaj GdJMdjdj dCfg jJhGab eY fhY GdOQGSI(B. (3dLeY GdHjGfGJ Je GSJNOGe GdGSJeGQI cCOGI ddOQGSI, oWHbJ Ydi YOO ef eYdej heYdeGJ HYV eJhSWGJ GdfHWjI, aGTJedJ GdYjfI Ydi (B79 (3eOQSI ehRYI Ydi (B46 (3eOQSI QSejI h(B33 (3eOQSI NGUI ZjQ eLGfjI(B. (3NdUJ GdOQGSI Edi GdfJGFL GdJGdjI(B: 1) (3hLhO CKQ cHjQ deJZjQ YeQ GdeYde hYOO SfhGJ GdNHQI heDgdg GdYdej Ydi echfGJ GdOGaYjI, Ohf Cf jKHJ Cj CKQ ege deJZjQ LfS GdeYde(B. 2) (3hLhO GQJHGW cHjQ HfSH YGdjI Hjf GdJbOjeGJ GdeGdjI hGROjGO GdOGaYjI, Ohf Cf jJCKQ GdCOGA GdaYdj dhGLHGJg HMLe gPg GdJbOjeGJ(B. 3) (3VYa MGdI GdQVG Yf XQha GdYed(B. 4) (3VYa aj HfGA HQGeL eHfjI Ydi GMJjGLGJ MbjbjI heOQhSI(B. 5) (3VYa aj bOQI GdeOQGA Ydi JMhjd GdegGe GdETQGajI GdQbGHjI Edi aQU dEYWGA GdJZPjI GdQGLYI GdEjLGHjI hJMSjf COGA GdeYde heSGfOJg dJWhjQ caGAJg(B.s
(3GdfhY (B: (3QSGdIs
Keywords: Cycle moyen; Gestion scolaire; Incitation pour enseignant; Intermediate Education; Teachers incentives School management; (3GdeQMdI GdeJhSWIs; (3OGaYjI GdeYdejf GdGOGQI GdeOQSjIs; (3bVGA GdfHWjIs